Supported dual‐acidic 1, 3‐disulfoimidazolium chlorozincate@HZSM‐5 as a promising heterogeneous catalyst for synthesis of indole derivatives. (27th January 2019) - Saikia, Susmita; Puri, Krishna; Borah, Ruli
Abstract : HZSM‐5‐supported Brönsted and Lewis acidic ionic solid 1, 3‐disulfoimidazolium chlorozincate materials ([dsim]2 [ZnCl4 ]@HZSM‐5) were synthesized with various ratios (3, 6, 9, 17 and 50% w/w). The heterogeneous materials were characterized via a variety of spectroscopic techniques. Dual acidity of these materials was determined using specified techniques. These acidic solids were examined as stable heterogeneous catalysts for the Fischer indole reaction of equimolar amounts of phenylhydrazine hydrochloride and various aliphatic or aromatic ketones at 80–90°C in neat condition to produce substituted indole derivatives. The efficient 17% ionic salt‐loaded HZSM‐5 composite was easily reused for ten consecutive cycles with a slight loss of its activity. The recycled catalyst was further analysed using powder X‐ray diffraction and inductively coupled plasma optical emission spectrometric techniques. Abstract : This work focused on synthesis and characterization of highly stable HZSM‐5‐supported Brönsted–Lewis acidic chlorozincate materials with various ratios, obtained via a wet impregnation method. Their structural variations along with catalytic effectiveness were studied for their use as heterogeneous catalysts for the Fischer indole reaction.